Phosphatidylethanolamine homeostasis under conditions of impaired CDP-ethanolamine pathway or phosphatidylserine decarboxylation - St Germain, Michaela; Iraji, Roya; Bakovic, Marica (Frontiers in Nutrition, 2023)
Phosphatidylethanolamine is the major inner-membrane lipid, which is synthesized in the endoplasmic reticulum (ER) from ethanolamine and diacylglycerol by the CDP-ethanolamine pathway and from phosphatidylserine by decarboxylation in the mitochondria. Recently, multiple genetic disorders that impact these pathways have been identified, including hereditary spastic paraplegia 81 and 82, Liberfarb syndrome, and a new type of childhood-onset neurodegeneration-CONATOC. Individuals with deficiencies in these pathways suffer from multisystem disorders mainly affecting neuronal function. This indicates the importance of maintaining proper phospholipid homeostasis when major biosynthetic pathways are impaired. This study summarizes the current knowledge of phosphatidylethanolamine metabolism in order to identify possible treatment options. The research indicates that targeting the lysoPE acylation pathway is a promising method of increasing PE in the case of deficiency as it can supply both the ER and mitochondrial PE pools, however more studies are needed to determine the best methods of doing this in vivo.